Teachers' perceptions of the Kampus Mengajar program in enhancing student literacy and numeracy - Puspitasari, Putri Anggraini; Budisantoso, Heri Triluqman (Universitas Negeri Semarang, 2024)
The Kampus Mengajar Program is one of the initiatives designed by the government to address literacy and numeracy issues among students in Indonesia through collaboration between university students and elementary school teachers. This study aims to explore teachers' perceptions of the Kampus Mengajar program in improving student literacy and numeracy. The research used a descriptive qualitative approach with a phenomenological design. Data collection techniques included interviews, observation, and documentation at an elementary school in Denpasar, Bali. The results showed that, overall, teachers perceive the Kampus Mengajar program positively, as reflected in their enthusiasm and active support for its implementation. The teachers understand the program's purpose, which is to improve students' literacy and numeracy skills. However, challenges arose during implementation, such as limitations in addressing all students' needs and a reduced implementation schedule. The program is considered to have successfully met students' needs and positively impacted on their literacy and numeracy skills. The findings offer important implications for the future development and improvement of the Kampus Mengajar program.